In vitro and in vivo evaluation of periosteum-derived cells and iPSC-derived chondrocytes encapsulated in GelMA for osteochondral tissue engineering - Agten, Hannah; Van Hoven, Inge; Van Hoorick, Jasper; Van Vlierberghe, Sandra; Luyten, Frank P.; Bloemen, Veerle (Frontiers in Bioengineering and Biotechnology, 2024)
Osteochondral defects are deep joint surface lesions that affect the articular cartilage as well as the underlying subchondral bone. In the current study, a tissue engineering approach encompassing individual cells encapsulated in a biocompatible hydrogel is explored in vitro and in vivo. Cell-laden hydrogels containing either human periosteum-derived progenitor cells (PDCs) or human induced pluripotent stem cell (iPSC)-derived chondrocytes encapsulated in gelatin methacryloyl (GelMA) were evaluated for their potential to regenerate the subchondral mineralized bone and the articular cartilage on the joint surface respectively. PDCs are easily isolated and expanded progenitor cells that are capable of generating mineralized cartilage and bone tissue in vivo via the process of endochondral ossification. iPSC-derived chondrocytes are an unlimited source of stable and highly metabolically active chondrocytes. Cell-laden hydrogel constructs were cultured for up to 28 days in a serum-free chemically defined chondrogenic medium. On day 1 and day 21 of the differentiation period, cell-laden constructs were implanted subcutaneously in nude mice to evaluate ectopic tissue formation 4 weeks post-implantation. Taken together, the data suggests that iPSC-derived chondrocytes encapsulated in GelMA can generate hyaline cartilage-like tissue constructs with different levels of maturity, while using periosteum-derived cells in the same construct type generates mineralized tissue and cortical bone in vivo. Therefore, the aforementioned cell-laden hydrogels can be an important part of a multicomponent strategy for the manufacturing of an osteochondral implant.